Tornado of Life: A Doctor's Journey through Constraints and Creativity in the ER - Baruch, Jay (Cambridge, Massachusetts : The MIT Press, 2022)
"An exploration of how caring for ER patients is more than blood and mayhem. It is the practice of being attentive to patients complicated and often broken stories as well as their broken bodies."
Keywords: Emergencies -- psychology; Physician-Patient Relations; Emergency Treatment; Emergency Service, Hospital